Case Study of Vida EV by Hero MotoCorp: Creating new industry vertical through electric vehicles (Journal of Finance, Business and Management Studies, 2024)
The abstract explores the transformative potential of electric vehicles (EVs) in creating a novel industry vertical. As global concerns about environmental sustainability and the need for clean energy solutions intensify, EVs emerge as a key driver for fostering innovation and establishing new economic sectors. This paper delves into the multifaceted aspects of leveraging EV technology to create a distinct industry vertical. It examines the shift from conventional fossil fuel-powered vehicles to EVs, highlighting the environmental benefits and the role of governmental policies in driving this transition.The study investigates how the EV ecosystem, including manufacturing, infrastructure development, and supply chains, contributes to the formation of a unique industry vertical in Hero MotoCorp. The analysis encompasses the financial incentives provided by governments to stimulate EV adoption, technological advancements, and the potential for job creation within the emerging EV sector. Additionally, the abstract underscores the importance of strategic collaborations between stakeholders, such as automotive manufacturers, energy providers, and policymakers, to facilitate the growth of this nascent industry vertical. Ultimately, the research contends that embracing electric vehicles has the potential not only to revolutionize transportation but also to catalyze the emergence of a dynamic and sustainable industry with far-reaching economic and environmental implications.
Keywords: Industry verticals; Electric vehicles; Hero Vida